Small Bowel Obstruction After Neonatal Repair of Congenital Diaphragmatic Hernia—Incidence and Risk-Factors Identified in a Large Longitudinal Cohort-Study - Zahn, Katrin B.; Franz, Anna-Maria; Schaible, Thomas; Rafat, Neysan; Büttner, Sylvia; Boettcher, Michael; Wessel, Lucas M. (Frontiers in Pediatrics, 2022)
In patients with congenital diaphragmatic hernia (CDH) postoperative small bowel obstruction (SBO) is a life-threatening event. An incidence of 20% and an association with patch repair and ECMO-treatment have been reported. Adhesions develop due to peritoneal damage and underly various biochemical and cellular processes. This longitudinal cohort study aimed at identifying the incidence of SBO and risk factors of surgical, pre- and postoperative treatment. We evaluated all consecutive CDH survivors born between January 2009 and December 2017 participating in our prospective long-term follow-up program with a standardized protocol. 337 patients were included, with a median follow-up of four years. SBO with various underlying causes was observed in 38 patients (11.3%) and significantly more often after open surgery. The majority of SBO required surgical intervention (92%). Adhesive SBO (ASBO) was detected as the leading cause in 17 of 28 patients, in whom surgical reports were available. Duration of chest tube insertion (OR 1.22; 95% CI 1.01–1.46, p=0.04) was identified as an independent predictor for ASBO in multivariate analysis. Beyond the cut-off value of 16 days, the incidence of serous effusion and chylothorax was higher in ASBO-patients (ASBO/nonSBO: 2/10 vs. 3/139 serous effusion, p=0.04; 2/10 vs. 13/139 chylothorax, p=0.27). Type of diaphragmatic reconstruction, abdominal wall closure or ECMO-treatment showed no significant association with ASBO. A protective effect of one or more reoperations has been detected (RR 0.16; 95% CI 0.02–1.17; p=0.049). Thoracoscopic CDH-repair significantly lowers the risk of SBO - however, not every patient is suitable for this approach. GoreTex®-patches do not seem to affect the development of ASBO, while median laparotomy might be more favourable than a subcostal incision. Neonates produce more proinflammatory cytokines and have a reduced anti-inflammatory capacity, which may contribute to the higher incidence of ASBO in patients with longer duration of chest tube insertion, serous effusion and chylothorax– as well as to the protective effect of reoperations. In future, novel therapeutic strategies based on a better understanding of the biochemical and cellular processes involved in the pathophysiology of adhesion formation might contribute to a reduction of peritoneal adhesions and their associated morbidity and mortality.